The Legal Harmonization in Bankruptcy Arrangements in the Notary Profession - Purnamasari, Dyah Putri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
Notary profession can be dishonorably dismissed if declared bankrupt by a court decision regulated in article 12 letter a of Act No. 2 of 2014 concerning Amendments to Act No. 30 of 2004 Position of Notary. The provisions of this article contradict the provisions of the Bankruptcy and Suspension of Obligations for Payment of Debt Law No. 37 of 2004 which cover the subject of bankruptcy, the object of bankruptcy and the legal consequences of bankruptcy. This legal research aims to find out and analyze the harmonization of the Law on Notary Office and the Law on Bankruptcy and Suspension of Debt Payment Obligations, especially the Notary Profession declared bankrupt and to know and analyze legal certainty for the Notary profession declared bankrupt. This study uses a normative juridical approach using analytical descriptive research specifications. The type of data in this legal research is normative by using primary legal materials in the form of various laws and regulations related to bankruptcy law for the Notary profession. Secondary legal materials are in the form of journals, both international and national journals, opinions of legal scholars, papers, research reports, articles and magazines as well as literature and electronic libraries related to legal protection. As well as tertiary legal materials in this study in the form of legal dictionaries, Indonesian dictionaries and encyclopedias. The method of collecting data in this study is in the form of literature and the method of data analysis used is in the form of legal logic with the deductive method. Based on the results of the research and discussion, disharmony was found between the Law on Notary Office and the Bankruptcy Law regarding the regulation of the profession of a Notary who was declared bankrupt both in terms of the subject of bankruptcy, the object of bankruptcy and the legal consequences of bankruptcy for the Notary profession. Then it was found that there were multiple interpretations in article 12 letter (a) of the Notary Office Law, causing legal uncertainty and injustice for Notaries who were declared bankrupt.Keywordsci: Bankruptcy; Harmonization; Profession.